Safety in lumbar puncture, nursing care before and after cerebrospinal fluid collection (Research, Society and Development, 2025)
Cerebrospinal Fluid (CSF) is an essential fluid for the protection and homeostasis of the central nervous system. During a lumbar puncture, a sample of this fluid is withdrawn for examination, which is highly relevant for the diagnosis of various pathologies. This article aims to investigate the safety of lumbar puncture in patients requiring the examination and the nursing care required before, during, and after CSF collection. This is a literature review conducted between August 15 and November 12, 2025, using databases such as Guyton, ANVISA, the Ministry of Health, SciELO, and various scientifically proven articles. Nineteen studies, in Portuguese and English, addressing the topic were included. The results showed that the main nursing care considerations relate to the proper preparation and positioning of the patient, and the importance of good aseptic practices before, during, and after the procedure. 70% of the examinations performed were uneventful. We emphasize that continuing education and the standardization of care protocols reduce risks and lead to improvements in the quality of care. Therefore, the role of nursing is to be one of the pillars that ensure patient safety.